The Effect of Curcumin-Loaded Glucan Nanoparticles on Immune Cells: Size as a Critical Quality Attribute - Mariana Colaço; Tiago Roquito; João Panão Costa; Maria Teresa Cruz; Olga Borges (MDPI AG, 2023)
Curcumin is known for its multiple health benefits, largely due to its antioxidant and anti-inflammatory properties. It has been extensively studied as a therapeutic agent, however, it does not have good clinical efficacy due to its poor water solubility and bioavailability. Despite accepting the encapsulation of this compound in polymeric particles as one of the most promising strategies to increase its therapeutic value, these nanoparticles have fallen short of expectations due to a lack of assessment of their possible adverse effects on the immune system. Therefore, in this work, we report on a new method to encapsulate curcumin into glucan nanoparticles and their effects on cells of the immune system were evaluated. Two different-sized curcumin-loaded glucan NPs (GluCur 100 and GluCur 380) were produced, each with an encapsulation efficiency close to 100%, and were characterized regarding their size distribution, surface properties, and morphology. The results revealed the greatest hemolytic effect and cytotoxicity for the smallest particles (100 nm) tested in human PBMCs and RAW 264.7 cells. Although GluCur 380 NPs showed a weaker ROS production, they were able to inhibit the production of NO by macrophages. Furthermore, we found that the coagulation time was not affected by both sized-particles as well as platelet function. Additionally, both nanoparticles induced lymphocyte proliferation and TNF-α secretion by Mo-DCs. In conclusion, this report emphasizes the importance of the immunotoxicity assessment and how this is dependent on the intrinsic properties of nanomaterials, hopefully contributing to increasing the safety of nanomedicines.